The “Knowledge Marketing”: a New Trend in a Management Science World - Curbatov, O.Yu. (Економічний вісник Донбасу, 2013)
This communication reports on the progress of a research based on a conceptual analysis of consumer’s competencies, as defined in Knowledge Marketing research and aims at proposing a new model of competencies for a better understanding of the value created by the consumer and the firm. The conceptual framework is illustrated by the use of the Smell Web (Exhalia Project). This illustration is elaborated from a secondary exploitation of a qualitative research. This communication takes into account the polysemy of the notion of competency and tries to contribute to the enrichment of current theoretical and managerial works on value co-creation. Цю статтю присвячено прогресу в дослідженні основ концептуального аналізу споживчої компетентності, визначенню маркетингового дослідження знання. Вона має на меті пропозицію нової моделі компетентності для кращого розуміння значення, створено- го споживачем і фірмою. Концептуальну структуру ілюструє використання Павутини Запаху (Проект Exhalia). Ця ілюстрація детально розглянута в другій частині дослідження. Ця стаття бере до уваги множинність поняття компетентності та сприяє збагаченню теоретичних і управлінських робіт із створення вартості. Эта статья посвящена прогрессу в исследовании основ концептуального анализа потребительской компетентности, определению маркетингового исследования знания и имеет целью предложение новой модели компетентности для лучшего понимания значения, созданного потребителем и фирмой. Концептуальную структуру иллюстрирует использование Паутины Запаха (Проект Exhalia). Эта иллюстрация детально рассмотрена во второй части исследования. Эта статья принимает во внимание множественность понятия компетентности и содействует обогащению теоретических и управленческих работ по созданию стоимости.